Chronic lymphocytic leukaemia and Richter's transformation: multimodal review and new imaging paradigms. Issue 11 (November 2021) - Musanhu, E.; Sharma, R.K.; Attygalle, A.; Wotherspoon, A.; Chau, I.; Cunningham, D.; Dearden, C.; El-Sharkawi, D.; Iyengar, S.; Sharma, B.
Abstract : Chronic lymphocytic leukaemia (CLL) is the most common leukaemia in adults. It is a malignancy of CD5 B-cells characterised by small, mature-appearing lymphocytes accumulating in the blood, bone marrow, and lymphoid tissues. Richer transformation (RT) is an important adverse complication. Detection of RT is critical to allow initiation of appropriate therapy. CLL staging and response evaluation is complicated and nuanced. From our extensive tertiary centre experience of several hundred CLL cases over the last decade, we detail key computed tomography (CT) and positron-emission tomography (PET) imaging features of the natural history of CLL. The authors present an original imaging-based patient-management paradigm for the investigation of potential RT, which will inform global practice. Potential applications of whole-body diffusion weighted imaging, novel PET radiotracers, minimal residual disease, and ct-DNA are addressed. Highlights: Imaging is not routinely indicated for Chronic Lymphocytic Leukaemia surveillance. In Richter transformation investigation, PET-CT is used to identify biopsy sites, tissue is needed for histological confirmation. Novel therapy agents may interfere with the interpretation of PET-CT data in CLL patients being investigated for Richter Transformation.